2019
DOI: 10.1080/1478422x.2019.1605472
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the corrosion resistance of an Al–Cu alloy and an Al–Cu–Li alloy

Abstract: In this study, the corrosion mechanisms of the AA2024-T3 and the AA2098-T351 were investigated and compared using various electrochemical techniques in 0.005 mol L −1 NaCl solution. The severe type of corrosion in the AA2098-T351 was intragranular attack (IGA) although trenching and pitting related to the constituent particles were seen. On the other hand, the AA2024-T3 exhibited severe localised corrosion associated with micrometric constituent particles, and its propagation was via grain boundaries leading t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
21
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 49 publications
1
21
0
1
Order By: Relevance
“…These alloys are reported to have low density, good mechanical strength, and good toughness [ 4 , 5 , 6 ]. Al-Cu-Li alloys, such as 2098, present a reduction in Li content compared to previous first and second generation alloys [ 2 , 7 ], and this reduction causes greater toughness compared to alloys from previous generations [ 5 , 6 ]. This feature represents a significant advantage, since low toughness characteristics were a disadvantage in previous Al-Li alloys.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…These alloys are reported to have low density, good mechanical strength, and good toughness [ 4 , 5 , 6 ]. Al-Cu-Li alloys, such as 2098, present a reduction in Li content compared to previous first and second generation alloys [ 2 , 7 ], and this reduction causes greater toughness compared to alloys from previous generations [ 5 , 6 ]. This feature represents a significant advantage, since low toughness characteristics were a disadvantage in previous Al-Li alloys.…”
Section: Introductionmentioning
confidence: 99%
“…This feature represents a significant advantage, since low toughness characteristics were a disadvantage in previous Al-Li alloys. The 2098 Al-Cu-Li alloy has a chemical composition that contains elements such as Cu, Li, Mg, Mn, Zr, Ag and Ti responsible for its advanced microstructure [ 7 , 8 ]. The main phase responsible for the good mechanical properties of Al-Cu-Li alloys is the T1 phase (Al 2 CuLi) [ 2 , 7 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Williams and Starke [11] stated that these Al-Li alloys can be considered optimal candidates for aerospace and aircraft vehicles, due to low density, high speci c modulus and speci c strength, the same consideration has been drawn by Goebel et al a latest study considering the latest developments of Al-Li alloys. Yin et al [12] reported that the alloys belonging to the recently developed third generation of damage-tolerant Al-Li alloys, such as AA2198, demonstrated relatively higher mechanical properties, Zhang S. et al [13] stated that these high mechanical properties can be attributable mostly to the precipitation of the T 1 (Al 2 CuLi) phase, whereas Milagre et al [14] proved that the attendance of Li lower density and enhance stiffness. In contrast Xu et al [15] and lately Krug et al [16] reported that the previous generations of Al-Li alloys, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Embora toda a amostra tenha sofrido ataque localizado, menor quantidade de produtos de corrosão foi formada sobre a ZM Figura 48 (e) do que sobre o MB Figura 48 (d). Convém ressaltar que, devido à elevada agressividade da solução utilizadaneste ensaio, algumas das características da CLS (tais como: área protegida catodicamente ao redor do centro do pite e anel de produtos de corrosão[9,14,15,108,127]) não foram observadas.…”
unclassified